Regulation of Ca2+ mobilization by prolactin in mammary gland cells: Possible role of secretory pathway Ca2+-ATPase type 2 - Utchariya Anantamongkol (2018)
Regulatory role of prolactin (PRL) on Ca2+mobilization in human mammary gland cell line MCF-7 was examined. Direct addition of PRL did not affect cytoplasmic Ca2+concentration ([Ca2+]i); however, treatment with PRL for 24 h significantly decreased the peak level and duration time of [Ca2+]ielevation evoked by ATP or thapsigargin (TG). Intracellular Ca2+release by IP3or TG in permeablized cells was not decreased after PRL-treatment, indicating that the Ca2+release was not impaired by PRL treatment. Extracellular Ca2+entry evoked by ATP or TG was likely to be intact, because entry of extracellular Ba2+was not affected by PRL treatment. Among Ca2+-ATPases expressed in MCF-7 cells, we found significant increase of secretory pathway Ca2+-ATPase type 2 (SPCA2) mRNA in PRL-treated cells by RT-PCR experiments including quantitative RT-PCR. Knockdown of SPCA2 by siRNA in PRL-treated cells showed similar Ca2+mobilization to that in PRL-untreated cells. The present results suggest that PRL facilitates Ca2+transport into Golgi apparatus and may contribute the supply of Ca2+to milk. © 2006 Elsevier Inc. All rights reserved.